Forest damage and subsequent recovery alter the water composition in mountain lake catchments - Schmidt, Susanne I; Hejzlar, Josef; Kopáček, Jiří; Paule-Mercado, Ma Cristina; Porcal, Petr; Vystavna, Yuliya; Lanta, Vojtěch (The Science of the total environment, 2022)
Forest damage by insect infestation directly affects the trees themselves, but also indirectly affects water quality via soil processes. The changes in water composition may undergo different pathways depending on site-specific characteristics and forest components, especially the proportion of coniferous and deciduous trees. Here, we test whether changes in forest components and the intensity of disturbance can predict the chemical properties of water outflow from affected lake catchments. Information about forest regeneration (a phase dominated by deciduous trees) and the proportions of damaged and healthy coniferous trees and treeless areas were obtained from satellite data. The four study catchments of Prášilské, Laka, Plešné, and Čertovo lakes are geographically close and located in the same mountain range (Šumava Mts., Czech Republic) at similar altitude, but they differ in extents of forest disturbances and recoveries. The water quality measured at the lake catchment outflows differed, and better reflected the development of forest components and health than did meteorological (temperature and precipitation) or hydrological (discharge) variables. Several of the outflow properties (concentrations of inorganic aluminium, protons, potassium, calcium, magnesium, alkalinity, dissolved organic carbon (DOC), nitrate, and total phosphorus), responded catchment-specifically and with different delays to forest disturbance. The most pronounced differences occurred in DOC concentrations, which started to increase in the most disturbed Plešné and Laka catchments 7 and 6 years, respectively, after the peak in tree dieback, but did not increase significantly in the Prášilské catchment, which was disturbed several times during the last 3-4 decades. This study demonstrates an importance of extents of forest disturbances, the following changes in forest composition, and catchment-specific characteristics on water composition.
Keywords: stromy; Soil; jezera; Remote sensing; cFII; Lake outflow water quality; Forest components; Forests; Mountain lake catchments; hydrologie; Insect infestation; Hydrology; lesy; Trees; Lakes; půda